"The story of data": A socio-technical approach to education for the data librarian role in the CityLIS library school at City, University of London. Issue 6 (15th August 2017) - Robinson, Lyn; Bawden, David
Abstract : Purpose: The purpose of this paper is to describe a new approach to education for library/information students in data literacy – the principles and practice of data collection, manipulation and management – as a part of the Masters programmes in library and information science (CityLIS) at City, University of London. Design/methodology/approach: The course takes a socio-technical approach, integrating, and giving equal importance to, technical and social/ethical aspects. Topics covered include: the relation between data, information and documents; representation of digital data; network technologies; information architecture; metadata; data structuring; search engines, databases and specialised retrieval tools; text and data mining, web scraping; data cleaning, manipulation, analysis and visualisation; coding; data metrics and analytics; artificial intelligence; data management and data curation; data literacy and data ethics; and constructing data narratives. Findings: The course, which was well received by students in its first iteration, gives a basic grounding in data literacy, to be extended by further study, professional practice and lifelong learning. Originality/value: This is one of the first accounts of an introductory course to equip all new entrants to the library/information professions with the understanding and skills to take on roles in data librarianship and data management.